Survival and Flight Capacity of Apis mellifera after Contact with Residues of Spiromesifen on Melon Leaves - Alesia Alves de Souza; Emanoely Karoliny Santos da Silva; Ewerton Marinho da Costa; Tiago Augusto Lima Cardoso; Jacquelinne Alves de Medeiros Araújo Costa; Daiane Mirian Tomaz da Silva; Ancélio Ricardo de Oliveira Gondim (Sociobiology)
Balancing the application of insecticides with the preservation of bees in agricultural areas poses a significant challenge to farmers. Therefore, this study aims to assess the survival and flight capacity of Apis mellifera (L.) bees after contact with residues of the insecticide/acaricide Spiromesifen on melon leaves. The experiment occurred under laboratory conditions, in a completely randomized design and a 4x3 factorial scheme, with two doses of Spiromesifen (0.24 and 0.288 g a.i./L), a positive control (Thiamethoxam), and an absolute control (distilled water), at three exposure times: 1, 2, and 3 hours after treatment application. Spiromesifen caused mortality of 15.33% and 13.80% after 1 hour of spraying, 20.05% and 17.72% after 2 hours of spraying, and 21.52% and 14.33% after 3 hours of spraying, for lower and higher doses, respectively. Spiromesifen provided a median lethal time of 112.9 hours, regardless of dose and exposure time. After exposure to the lower dose of Spiromesifen at 1, 2, and 3 hours after spraying, 28.41%, 8.0%, and 17.0% of the bees were able to fly, respectively, while at the higher dose, 33.55% and 8.11% were able to fly after 1 and 2 hours of spraying. Bees exposed after 3 hours of spraying at the higher dose showed a flight activity similar to the absolute control. Contact with Spiromesifen residues on melon leaves was slightly lethal to the honey bee A. mellifera, but it reduced the flight capacity of surviving bees after exposure.